Perbedaan Hasil Belajar Menggunakan Model Pembelajaran Kooperatif Tipe Student Team Achievement Divisions Berbantu Modul Dengan Pembelajaran Ceramah Dalam Mata Pelajaran Kewirausahaan Kelas XI SMK Negeri 1 Padang - Hendrayanti, Lusi; Tanjung,, Mirna; Sriwahyuni, Sriwahyuni (Pendidikan Ekonomi, 2014)
Â ABSTRACTÂ This research has a background by less. It is caused by lock of studentâs activities in the learning process because the method just focus on teacher. The research aims to know any diffrencess of result study of student entrepreneurship with cooperative learning model tipe STAD better than the result study by using conventional learning on the second year of SMK N 1 Padang. Based on result of analyze data got eksperimental class mean score was 81,08 and 71,61 for the control class. Then, hyphothesis testingwas used Z test by using SPSS 15.0 version, got the score of Z calculate 5,094 bigger that table Z 2,00, wich mean that hyphothesis was accepted on the real significant Î± (0,05). It was concluded that the result study of student entrepreneurship through cooperative learning model tipe STAD better that conventional learning Â on second year class of SMK N 1 Padang.Â